A study of digital presentation techniques in architecture - David C. Chang; Peter Szalapaj (2000)
Since the successful application of computer animation in the film and video-game industries, we have seen a rise in the general education of people in the areas of graphics and audio-visual media. In contrast, the average level of understanding of architectural representation is still much lower than it is with regard to other visual media. Architectural presentations are of great importance in revealing how the built environment is conceptualised, constructed and perceived. As media types may vary, their contribution to the creation of the built environment differs too. Writings allow readers to envisage images in their minds, while perspectives and computer graphics provide more realistic and objective images, although still restricted to flat surfaces. Contemporary technology permits architects and clients to virtually visit 'the buildable'. The core problem of these presentations, however, is how to interpret them, as they represent different motivations, attitudes and values. There has been no clear conception or definition of the nature and consistency of architectural space. The need for its representation and mass diffusion perhaps has consequently not been exploited as much as it should have been. This paper investigates the nature and characteristics of architectural presentation in the context of contemporary computer graphics technology.